A review of postsurgical dysphagia in nonmalignant disease. Issue 6 (December 2016) - Vansant, Mathew B.; Kunduk, Melda; McWhorter, Andrew J.
Abstract : Purpose of review: This article reviews current literature regarding postsurgical dysphagia in nonmalignant disease examining the current recommendations, risk factors, and potential implications. Recent findings: Surgical interventions including anterior cervical spine surgery, thyroidectomy, laryngeal and pulmonary, cardiac, esophageal and fundoplication, gastric and bariatric, and posterior fossa surgeries are known to result in swallowing dysfunction. Postsurgical dysphagia may increase the length of hospitalization, overall cost, risk of pneumonia, and time to oral intake. There are limited prospective research studies examining postsurgical dysphagia and poorly understood causes. The results are unclear regarding severity, symptom type, duration, and treatment outcomes of postsurgical dysphagia. Summary: The life-changing and life-threatening nature of dysphagia make this an important factor to consider and discuss with patients and families. Both acute and late-onset dysphagia may become chronic if left untreated. Presurgery and postsurgery swallow studies should be considered for cervical spine, thyroid, lung, gastric, cardiac, and surgeries involving the cranial nerves. Future research should examine postsurgical dysphagia in a prospective manner using established and reliable methods of measurement to parse out causal factors and more accurate prevalence rates for each surgical intervention and population.